Pemanfaatan CRISPR-Cas9 pada Antibodi Monoklonal untuk Terapi HIV - Adhytama S, Ryan Putra; Hala, Yusminah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
HIV infection remains a global health challenge with high rates of new infections and low levels of viral suppression, especially in middle-income countries. Antiretroviral therapy (ART) has significantly reduced morbidity and mortality, but has not been able to eliminate latent reservoirs so lifelong therapy remains necessary. In the last decade, monoclonal antibodies, particularly broadly neutralizing antibodies (bNAbs), as well as CRISPR-Cas9 gene-editing technology have emerged as innovative therapeutic approaches with long-term remission potential. bNAbs is able to neutralize a broad spectrum of HIV strains and activate immune effector mechanisms, including antibody-dependent cellular cytotoxicity (ADCC) and phagocytosis, but cost limitations, viral resistance, and duration of effects limit its use as a substitute for ART. In parallel, CRISPR-Cas9 has demonstrated the ability to target HIV proviruses in the host cell genome and enable the engineering of immune cells to stably produce therapeutic antibodies. Pre-clinical studies show that B-cell engineering with CRISPR-Cas9 can maintain immune memory, perform isotype switching, and somatic hypermutation, thus creating